CHARACTER-BUILDING FOR LAW STUDENTS: EXPLORING THE SATJIPTO RAHARDJO’S THOUGHTS - Herlindah Herlindah; Siti Rohmah; Ahmad Qiram As-Suvi (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2022)
The quality of law enforcement is determined by the character-building in the Faculty of Law. If so far, Indonesia is often faced with various poor quality law enforcement, and this portrait certainly does not occur naturally, but rather because the law faculty has not been able to play its role optimally in building the character of prospective law enforcers. This study explores Satjipto Rahardjo's thoughts on character-building for law enforcers at the faculty of law. The research method used in this article is a literature study with a qualitative descriptive approach using content analysis. The result of this study indicates that according to Satjipto Rahardjo, legal education at the Faculty of Law must be reoriented from the formation of a positivistic character to the formation of a progressive character of law that prioritizes ethical and moral values